Effects of knowledge levels and warning of impending time pressure on work performance - Lai, Victor Kuan Loong (2008)
This research project investigates whether people are able to adapt to time pressure conditions depending on whether they have superior knowledge and whether they are given warning of impending time pressure. We measured work performance under these conditions across task with varying complexity levels.